PEMETAAN MEDAN GEOPATIS SEBAGAI SALAH SATU KONSTRAIN PADA PERENCANAAN ZONING DAN BLOCKING INTERIOR RUMAH TINGGAL, Kasus Studi : Lahan di Jalan Budi Indah no.9: https://doi.org/10.25124/idealog.v3i2.1515 - sihombing, stella sondang (Universitas Telkom, 2018)
Humans are part of this universe thousands of years ago has developed a sense to detect the presence of energi from the earth itself or the so-called flow field geopatis. This energi can be separated into positive and negative energy. Negative energy generated by the flow field can lead to human become ill if man is above the flow for a long times. To avoid that, humans above the soil surface must move up to other place for become healthy. People build homes for they shelter, grow and develop. Nearly a third of human life is spent in the home and about 6 to 8 hours a day humans do rest to get the energy back to move well and healthy physically and mentality. This study tries to map the flow of negative terrain geopatis that exist in a land occupancy by using a special tool in order to avoid the flow pattern field geopatis. So that a planner residential design can plan zoning and blocking the right so that people who live in it can avoid the flow negatif. Also proff that maping the flow of negatif terrain geopatis can support space planning especialy for residential plan.